Surgical and Peri-Operative Considerations for Brain Metastases - Gupta, Saksham; Dawood, Hassan; Giantini Larsen, Alexandra; Fandino, Luis; Knelson, Erik H.; Smith, Timothy R.; Lee, Eudocia Q.; Aizer, Ayal; Dunn, Ian F.; Bi, Wenya Linda (Frontiers in Oncology, 2021)
Introduction Brain metastases are the most common brain tumors in adults, whose management remains nuanced. Improved understanding of risk factors for surgical complications and mortality may guide treatment decisions. Methods A nationwide, multicenter analysis was conducted with a retrospective cohort. Adult patients in the 2012-2015 American College of Surgeons National Surgical Quality Improvement Project (ACS NSQIP) databases who received a craniotomy for resection of brain metastasis were included. Results 3500 cases were analyzed, of which 17% were considered frail and 24% were infratentorial. The most common 30-day medical complications were venous thromboembolism (3%, median time-to-event [TTE] 4.5 days), pneumonia (4%, median TTE 6 days), and urinary tract infections (2%, median TTE 5 days). Reoperation and unplanned readmission occurred in 5% and 12% of patients, respectively. Infratentorial approach and frailty were associated with reoperation before discharge (OR 2.0 for both; p=0.01 and p=0.03 respectively), but not after discharge. Infratentorial approaches conferred heightened risk for readmission for hydrocephalus (OR 5.1, p=0.02) and reoperation for cerebrospinal fluid diversion (OR 7.1, p<0.001).Overall 30-day mortality was 4%, with nearly three-quarters occurring after discharge. Pre-frailty and frailty were associated with increased odds for post-discharge mortality (OR 1.7 and 2.7, p<0.05), but not pre-discharge mortality. We developed a model to identify pre-/peri-operative variables associated with death, including frailty, thrombocytopenia, and high American Society of Anesthesiologists score (AUROC 0.75). Conclusions Optimization of metrics contributing to patient frailty and heightened surveillance in patients with infratentorial metastases may be considered in the peri-operative period.